Sleep Restriction Therapy for Insomnia is Associated with Reduced Objective Total Sleep Time, Increased Daytime Somnolence, and Objectively Impaired Vigilance: Implications for the Clinical Management of Insomnia Disorder - Kyle, Simon D.; Miller, Christopher B.; Rogers, Zoe; Siriwardena, A. Niroshan; MacMahon, Kenneth M.; Espie, Colin A. (Sleep (New York, N.Y.), 2014)
To investigate whether sleep restriction therapy (SRT) is associated with reduced objective total sleep time (TST), increased daytime somnolence, and impaired vigilance. Within-subject, noncontrolled treatment investigation. Sleep research laboratory. Sixteen patients [10 female, mean age = 47.1 (10.8) y] with well-defined psychophysiological insomnia (PI), reporting TST ≤ 6 h. Patients were treated with single-component SRT over a 4-w protocol, sleeping in the laboratory for 2 nights prior to treatment initiation and for 3 nights (SRT night 1, 8, 22) during the acute interventional phase. The psychomotor vigilance task (PVT) was completed at seven defined time points [day 0 (baseline), day 1,7,8,21,22 (acute treatment) and day 84 (3 mo)]. The Epworth Sleepiness Scale (ESS) was completed at baseline, w 1-4, and 3 mo. Subjective sleep outcomes and global insomnia severity significantly improved before and after SRT. There was, however, a robust decrease in PSG-defined TST during acute implementation of SRT, by an average of 91 min on night 1, 78 min on night 8, and 69 min on night 22, relative to baseline (P < 0.001; effect size range = 1.60-1.80). During SRT, PVT lapses were significantly increased from baseline (at three of five assessment points, all P < 0.05; effect size range = 0.69-0.78), returning to baseline levels by 3 mo (P = 0.43). A similar pattern was observed for RT, with RTs slowing during acute treatment (at four of five assessment points, all P < 0.05; effect size range = 0.57-0.89) and returning to pretreatment levels at 3 mo (P = 0.78). ESS scores were increased at w 1, 2, and 3 (relative to baseline; all P < 0.05); by 3 mo, sleepiness had returned to baseline (normative) levels (P = 0.65). For the first time we show that acute sleep restriction therapy is associated with reduced objective total sleep time, increased daytime sleepiness, and objective performance impairment. Our data have important implications for implementation guidelines around the safe and effective delivery of cognitive behavioral therapy for insomnia.